Modernisation and governance in UK national governing bodies of sport: how modernisation influences the way board members perceive and enact their roles. Issue 3 (2nd July 2016) - Tacon, Richard; Walters, Geoff
ABSTRACT: Modernisation has been a key objective of many national governments for at least the last two decades. A significant element of the modernisation agenda has been the focus on improving the governance of public sector and, more recently, voluntary sector organisations. In the UK voluntary sport sector, this has involved policy statements, governance monitoring systems linked to public funding and a number of 'good governance' guides, aimed primarily at the boards of national governing bodies of sport (NGBs). Previous research has critically analysed modernisation and explored its effects, most often at a macro level. Very little research, to date, however, has looked at the influence of modernisation on the boards of NGBs. This article seeks to do just that, drawing on the first national survey of board-level governance in the UK and an in-depth, longitudinal case study of one UK-based NGB. It empirically examines which board roles NGBs consider most important and statistically compares large and small NGBs. It then draws on direct observation of board and committee meetings, in-depth interviews and analysis of key organisational documents to examine how modernisation influences the way board members perceive and enact their roles. In doing so, this article draws together the political science research on modernisation and the sport governance research on board roles and seeks to promote closer integration between these complementary streams of research.